In-House IgM Dot-Blot Assay for Serodiagnosis of Human Leptospirosis: Development, Standardisation, and Performance Evaluation - Roberta Morozetti Blanco; Elaine dos Santos Lima; Juliana Maira Watanabe Pinhata; Angela Pires Brandao; Eliete Caló Romero (Microorganisms, 2025)
Laboratory confirmation of human leptospirosis relies on serological tests, with the microscopic agglutination test (MAT) as the reference. However, due to its complexity, there is a need for a simpler and more accessible diagnostic method. This study aimed to standardise and develop an IgM dot-blot test with a whole-cell antigen from saprophytic Leptospira biflexa serovar Patoc for diagnosing human leptospirosis. After checkerboard titration standardisation, IgM dot-blot was performed with paired serum samples from 124 MAT-confirmed leptospirosis cases and 143 serum samples from healthy and diseased individuals as the control group. Repeatability and reproducibility were also evaluated. An IgM dot-blot kit was then developed and compared to the PanbioTM Leptospira IgM ELISA using 144 serum samples from patients with suspected leptospirosis. The IgM dot-blot showed a sensitivity of 58.1% and 96.0% when performed on acute and convalescent samples, respectively. Specificity was 94.4%. The repeatability and reproducibility of the IgM dot-blot showed 100% consistency. Comparison of IgM dot-blot and IgM ELISA showed almost perfect agreement, with a Kappa index of 0.81. The developed IgM dot-blot offers a robust alternative to existing methods, requiring minimal specialised equipment and fewer reagents than IgM ELISA. The good performance of this IgM dot-blot immunoassay makes it a promising tool for diagnosing human leptospirosis, potentially increasing diagnostic capacity, especially in places with limited resources.